Polygamy and Its Implications on Christianity in Southwest Nigeria: A Sociological Perspective - Ogunbiyi, David Oluwabukunmi; Adeyemo, Ajibade Adedayo; Olajugbagbe, Oyekunle Martins; Oyebanji, Israel Temitope (MAHABBAH: Journal of Religion and Education, 2025)
Polygamy remains a significant cultural and religious practice in Southwest Nigeria, often conflicting with Christian doctrines that emphasize monogamy. This study explores the implications of polygamy on Christianity, examining its theological, social, and legal dimensions. Using a mixed-methods approach, data was collected from Christian leaders and polygamous individuals across various denominations. Results indicate that while 81.2% of respondents consider polygamy sinful, 94.4% agree that polygamous individuals should be full church members. However, 87.1% strongly oppose allowing polygamous individuals in leadership roles. The study also reveals that polygamous families face emotional distress, gender inequality, and legal uncertainties. Children from polygamous homes reported the highest level of dissatisfaction (83.8%), citing neglect and inheritance conflicts. Findings indicate that while most churches consider polygamy sinful, they still allow polygamous individuals to be members, though they are restricted from leadership roles. The study also highlights the emotional and financial challenges faced by women and children in polygamous households, including gender inequality, psychological distress, and inheritance disputes. Additionally, Nigeria’s plural legal system complicates the recognition and regulation of polygamous unions. Despite the tensions between cultural traditions and Christian teachings, many respondents advocate for inclusivity while upholding monogamy as the ideal. The study recommends that churches offer support to polygamous families, clarify leadership policies, and promote legal reforms to protect women and children’s rights.